2022
DOI: 10.1177/03611981221094305
|View full text |Cite
|
Sign up to set email alerts
|

Access Benefits of Shared Autonomous Vehicle Fleets: Focus on Vulnerable Populations

Abstract: This research monetizes the access benefits of making shared autonomous vehicles (SAVs) available to residents of Texas’ Dallas-Fort Worth metroplex in the U.S. Residents’ willingness to pay for SAV access under different fares and modes was estimated and compared across the region’s 5,386 traffic zones, with emphasis on those housing the regions’ most vulnerable or access-limited travelers. Assuming a $0.50/mi SAV fare, the average per-person-trip benefit is estimated to be $0.64 per trip. With $0.50/mi SAV f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This may be related to the on-demand characteristic of the EVA Shuttle, which is inherently beneficial for mobility-impaired people as a door-to-door service is possible. Consequently, the research emphasizes the findings of Lee and Kockelman [26] that a particular focus in developing such services must be put on the appropriate access for this group of people. Access relates not only to the physical requirements of the busses and infrastructure but also to the booking process of an on-demand autonomous minibus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be related to the on-demand characteristic of the EVA Shuttle, which is inherently beneficial for mobility-impaired people as a door-to-door service is possible. Consequently, the research emphasizes the findings of Lee and Kockelman [26] that a particular focus in developing such services must be put on the appropriate access for this group of people. Access relates not only to the physical requirements of the busses and infrastructure but also to the booking process of an on-demand autonomous minibus.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, females, elderly, and mobility-impaired people are regarded to use autonomous minibuses less likely [20]. However, several studies present considerable advantages in such a service, especially for vulnerable groups such as mobilityimpaired people, if adequate access to the services is considered [26]. A recent study on Germany's first automated minibus fleet in a regular service could support the latter empirically.…”
Section: Autonomous Minibus Servicesmentioning
confidence: 99%
“…Wicki et al carried out a mode choice experiment within the context of a real bus operation in Neuhausen, Switzerland, and found that technology acceptance strongly influences the decision ( 24 ). Lee and Kockelman focused on the vulnerable population within their research and found that vulnerable people can strongly benefit from SAVs when access is guaranteed ( 25 ). Yap et al carried out a stated preference experiment for an autonomous last-mile transport for multimodal train trips and found that AVs could be an alternative for first-class train passengers ( 26 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…SAVs, a synthesis of TNCs and autonomous vehicles (AVs), promise to improve urban congestion, reduce vehicular emissions, and democratize transportation access [2]. Unlike human-operated vehicles (HOV), SAVs do not require a human driver, which significantly reduces operational costs and enables continuous operation without driver fatigue [3,4]. Therefore, SAVs are anticipated to boost mobility by cutting driver costs and overcoming human drivers' limitations, offering costeffective, convenient, and superior-quality transportation for various trip purposes [5].…”
Section: Introductionmentioning
confidence: 99%